(3JfRjg GdTQjYI GdeQahYI Yf GdCNHGQ GdTfjYI GdehVhYIs - (3Ydj Hf eMeO Hf Ydj Hf YQGb,J (B963 (3g` s ((3bGSe Hf jhfS GdeZQHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef HJfRjg GdTQjYI hHYO aEf ef GdegeGJ YfO Cgd GdYde hGdJbi eYQaI GdGMGOjK GdehVhYg Ydi SjO GdeQSdjf dJfbi s
(3BNQgG (B:s
(3hMOjK GfG ef Gddg hGdeDefhf efi bGd GHf Jjejg ai GdSHYI ehVhYI hbO TQYJ ai LeYgG ai JCdja jchf cGdPjd Ydi gPG GdJCdja Ef SGYO GdJjSjQ ef GddWja GdNHjQ hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B494s
Keywords: (3GdJhMjO hGdedd hGdfMds